2012
DOI: 10.5194/hess-16-4447-2012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the physical controls of regional patterns of flow duration curves – Part 2: Role of seasonality, the regime curve, and associated process controls

Abstract: Abstract. The goal of this paper is to explore the process controls underpinning regional patterns of variations of streamflow regime behavior, i.e., the mean seasonal variation of streamflow within the year, across the continental United States. The ultimate motivation is to use the resulting process understanding to generate insights into the physical controls of another signature of streamflow variability, namely the flow duration curve (FDC). The construction of the FDC removes the time dependence of flows… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 51 publications
2
78
0
Order By: Relevance
“…Thompson et al (2011) and Ye et al (2012) showed that not accounting for vegetation phenology can lead to poor predictions of both seasonal evaporation and runoff variability in the northeastern USA, and that a temperature correction that mimics the phenology can help to improve the predictions. More globally, Cayan et al (2001) showed that in areas of the world with significant deciduous forests, changes in transpiration associated with phenology can contribute to significant changes in seasonal runoff.…”
Section: H Liu Et Al: Soil Moisture Controls On Patterns Of Grass Gmentioning
confidence: 99%
“…Thompson et al (2011) and Ye et al (2012) showed that not accounting for vegetation phenology can lead to poor predictions of both seasonal evaporation and runoff variability in the northeastern USA, and that a temperature correction that mimics the phenology can help to improve the predictions. More globally, Cayan et al (2001) showed that in areas of the world with significant deciduous forests, changes in transpiration associated with phenology can contribute to significant changes in seasonal runoff.…”
Section: H Liu Et Al: Soil Moisture Controls On Patterns Of Grass Gmentioning
confidence: 99%
“…As recently re-iterated by Ye et al (2012), the dominant processes controlling runoff patterns are influenced by complex interactions of climate, vegetation and landscape factors. In the absence of detailed a priori knowledge on the dominant runoff processes and due to the contrasting characteristics of the three study catchments, a flexible modeling strategy was thus adopted (e.g.…”
Section: Hydrological Modelsmentioning
confidence: 99%
“…This structure has been investigated through the prism of signatures including the flood frequency curve (e.g., Robinson and Sivapalan, 1997), water balance partitioning Harman et al, 2011;Sivapalan et al, 2011a), flow duration curve Yaeger et al, 2012;Ye et al, 2012), recession curve (e.g., Wittenberg, 2003), preferred states in the soil moisture distribution (e.g., Western and Grayson, 2001), and seasonal variations in the fluxes measured at an eddy-flux tower . The study of regimes adopts the Darwinian approach of analyzing populations but in the temporal domain (understanding a population of events within a watershed).…”
Section: Variation Across Time: Regimes and Filteringmentioning
confidence: 99%